Comparison of susceptibility to a toxic alien toad (Bufo japonicus formosus) between predators in its native and invaded ranges. (20th October 2019) - Oyake, Narumi; Sasaki, Nayuta; Yamaguchi, Aya; Fujita, Hiroyuki; Tagami, Masataka; Ikeya, Koki; Takagi, Masaki; Kobayashi, Makoto; Abe, Harue; Kishida, Osamu
Abstract: To manage biological invasions effectively, the impacts of alien species on the demography and traits of native species must be known, but determining those impacts can be challenging. We used a comparative approach to gain insight into the impacts that an alien toad ( Bufo japonicus formosus ) might have on native Japanese predatory amphibians. We compared the susceptibility of native predator species to alien toad toxins in the alien‐invaded range and the susceptibility of closely related native predator species to the toxins in the alien toad's native range to investigate the impacts of an alien on a native species. Bufo japonicus formosus is native to Honshu, but was recently introduced to Hokkaido and Sado. In laboratory experiments, we compared individual mortality of predators exposed to a toad hatchling between novel predators on the toad‐invaded islands and ecologically similar congeneric or conspecific species on Honshu, where the toad is native. We also compared (1) the percentage of individuals that consumed a toad hatchling and (2) toxin resistance (i.e. survival and growth of individuals after toad consumption) between these two groups of predators, as mechanistic components behind the susceptibility of the predators to the toxic prey. The mortality of Rana pirica from all populations after consumption of a toad hatchling was almost 100%, and that of Hynobius retardatus ranged from 14 to 90%, depending on the population. In contrast, the mortality of Rana ornativentris and Hynobius nigrescens was near 0% regardless of population. These differences between congeneric predators were mostly due to differences in their toxin resistance. These results suggest that the alien toad is a potential threat to the novel amphibian predators on Hokkaido, although they also imply that the novel predators on Hokkaido have the potential to develop toxin resistance through adaptive evolution. However, this counteradaptation may have a higher chance of evolving in H. retardatus than in R. pirica because of differences in their genetic backgrounds.